Understanding Decisions to Internationalize by Small and Medium-sized Firms Located in an Emerging Market (2009)
We examined perceptions differentiating key Colombian decisionmakers in 168 SMEs who decided to either internationalize or remain domestic. An integrative model compares managerial perceptions of competitive, macro-environmental and neo-institutional factors. • Foreign MNEs in the home market significantly differentiated decisions to internationalize, as well as the presence of internationalizing domestic competitors, anticipated product acceptance, and internationalizing suppliers. • The lack of findings for some institutional and macro-environmental factors may reflect important contextual features of the Colombian business environment. © 2009 Gabler-Verlag.